2020
DOI: 10.1002/14651858.cd004010.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Pessaries (mechanical devices) for managing pelvic organ prolapse in women

Abstract: www.cochranelibrary.comPessaries (mechanical devices) for managing pelvic organ prolapse in women (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 71 publications
0
62
0
4
Order By: Relevance
“…In our case the patient had the history of using pessary for around 10 years before she came to our hospital. Despite the pessary, that placed into the vagina to restore pelvic anatomy and decrease prolapse symptoms, is the only available, nonsurgical rst-line intervention especially for high-risk surgical candidates with POP that can relieve prolapse and urinary symptoms, it can cause serious complications such as bleeding and ulceration [5] that our index patient also appeared. Although the pessary itself does not cause cervical cancer, but the underlying increasing chance of nonspeci c infection that above-mentioned with the repeated take out and put in of the pessary may be one considerable factor for the progression of disease, so that the cervical carcinogenesis and precancerous changes of the vagina that con rmed through postoperative pathological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our case the patient had the history of using pessary for around 10 years before she came to our hospital. Despite the pessary, that placed into the vagina to restore pelvic anatomy and decrease prolapse symptoms, is the only available, nonsurgical rst-line intervention especially for high-risk surgical candidates with POP that can relieve prolapse and urinary symptoms, it can cause serious complications such as bleeding and ulceration [5] that our index patient also appeared. Although the pessary itself does not cause cervical cancer, but the underlying increasing chance of nonspeci c infection that above-mentioned with the repeated take out and put in of the pessary may be one considerable factor for the progression of disease, so that the cervical carcinogenesis and precancerous changes of the vagina that con rmed through postoperative pathological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic organ prolapse (POP) is a common condition affecting mostly postmenopausal women, with a peak age prevalence at 60–69 years [ 1 , 2 ]. The symptoms significantly impair women’s daily activities and quality of life [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic organ prolapse (POP) is a common condition affecting mostly postmenopausal women, with a peak age prevalence at 60–69 years [ 1 , 2 ]. The symptoms significantly impair women’s daily activities and quality of life [ 1 , 3 ]. POP involves the descent of one or more perineal organs (uterus, bladder, and/or rectum) from the normal anatomic position into the vagina [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken PFMT for instance, although previous randomised controlled trials (RCTs) reported that patients in PFTM group reported significantly more improvement on POP symptoms than that in control group, the clinical importance of the differences observed and its long-term effect remain suspicious 9–11. Other factors, such as constrains on indications, incidence of complications and recurrence of POP symptoms, often limit the acceptance and application of these non-surgical treatment to a wider population 3 8 12 13…”
Section: Introductionmentioning
confidence: 99%